Analysis of the Application of the Local Government Information System (SIPD) in Realizing Transparency and Accountability at the Regional Finance and Revenue Management Agency (BPKPD) of Binjai City (Centralization) - Lisa Raihanatul Husna; Laylan Syafina; Tuti Anggraini (Universitas Muhammadiyah Sorong, 2026)
This study aims to analyze the implementation of the Regional Government Information System (SIPD) in realizing regional financial transparency and accountability in the Binjai City BPKPD, with a special focus on the transition period from SIMDA to SIPD. The research uses a descriptive qualitative approach with a case study design. Data was collected through semi-structured in-depth interviews with five informants, non-participatory observations, and a documentation study of the Binjai City BPKPD Strategic Plan 2025-2029. The analysis used the interactive model of Miles, Huberman, and Saldana (2014) which was interpreted through the six-dimensional model of the DeLone and McLean (2003) Model. The results of the study reveal an asymmetrical effectiveness profile: the quality of information and the use of the system are considered effective; the quality of the system and user satisfaction are quite effective; Meanwhile, the quality of service is less effective due to the absence of formal technical guidance. The net benefits are realized through real-time data transparency and a permanent audit trail, although the full potential of SIPD has not been fully realized as confirmed by the Binjai City BPKPD Strategic Plan 2025-2029.